Patrick McGrath : Directions and Transgressions. - Dupont, Jocelyn (Cambridge Scholars Pub., 2012)
This book is the first collected volume to be entirely dedicated to the work of contemporary Anglo-American writer Patrick McGrath. It follows the international conference that was held in his presence at Perpignan University, France, in May 2011. It comprises nine chapters (as well as an introduction and an index) written by scholars specializing in Gothic and American literature, each dealing with specific aspects of McGrath's work. The volume seeks to encompass the author's whole literary ...